Critical Professional Development: A Necessary Risk?. (March 2023) - Wrenn, Melissa; Gregory, Kristen; Gallagher, Jennifer
Amy Yarborough, a veteran teacher and curriculum resource leader in a rural district in Virginia, facilitates a professional learning community focused on social justice and equity-oriented instructional practices. When allegations of teaching critical race theory are reported via the state's email tip line and community social media groups, Amy is asked to present her professional learning community materials to the local school board. In the midst of stakeholder protests and media scrutiny, Amy must decide how to explain her professional decisions. Current and future educational leaders interested in issues related to race and equity will consider the roles of policy and the public in influencing teachers' lessons.